1981
DOI: 10.1152/ajpgi.1981.241.6.g461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fat feeding on intestinal alkaline phosphatase activity in tissue and serum

Abstract: Serum intestinal alkaline phosphatase activity is increased by fat feeding, but the mechanism of this increase is not fully understood. Fasting rats were fed a single feed of either corn oil (12 kcal) or an isocaloric elemental feed (Vivonex 100 HN). Changes in enzyme activity in the small bowel mucosa and serum were followed for 20 h. Only the fat-fed rats had increased serum enzyme activity, being maximal at 7 h and three times the fasting level. This resulted from an increase in the amount of enzyme protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…The serum ALP levels elevate in healthy humans or animals when lipids are administered in a test meal or a high-lipid diet is consumed (McDowell and Ross, 1966;Young et al, 1981;Deems et al, 1994). On the other hand, polyphenolic compounds have been shown to inhibit iron absorption (Zijp et al, 2000;Samman et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The serum ALP levels elevate in healthy humans or animals when lipids are administered in a test meal or a high-lipid diet is consumed (McDowell and Ross, 1966;Young et al, 1981;Deems et al, 1994). On the other hand, polyphenolic compounds have been shown to inhibit iron absorption (Zijp et al, 2000;Samman et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…ALP and DPPIV activities were assayed spectrophotometrically using p-nitrophenyl phosphate and glycyl-L-proline-p-nitroanilide (Sigma-Aldrich, St. Louis, MO), respectively, as substrates (Maroux et al 1973, Young et al 1982. Enzyme activities were expressed relative to the mucosal protein content, which was determined using bovine ␥-globulin as a standard (Bradford 1976).…”
Section: Methodsmentioning
confidence: 99%
“…Since then, numerous investigators (5,6,15,19,29,32) have confirmed this phenomenon. On the other hand, a carbohydrate or protein meal is incapable of stimulating IAP (3,12).…”
mentioning
confidence: 79%